2013
DOI: 10.4093/dmj.2013.37.4.278
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Skeletal Muscle in Development of Nonalcoholic Fatty Liver Disease

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is closely correlated with abnormal accumulation of visceral fat, but the role of skeletal muscle remains unclear. The aim of this study was to elucidate the role of skeletal muscle in development of NAFLD.MethodsAmong 11,116 subjects (6,242 males), we examined the effects of skeletal muscle mass and visceral fat area (VFA, by bioelectric impedance analysis) on NAFLD using by the fatty liver index (FLI).ResultsOf the total subjects (9,565 total, 5,293 males) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 38 publications
(47 reference statements)
7
76
0
Order By: Relevance
“…engagement in resistance training, when strength was excluded from the model. This is consistent with the observations that skeletal muscle mass was inversely associated with FLI values [32] and that muscle fat accumulation correlated with NASH severity [33]. Altogether, these data point to a role of skeletal muscle, in addition to adipose tissue, in the pathogenesis of NAFLD.…”
Section: Mechanisms Of Exercise-induced Reduction In Fli and Vaisupporting
confidence: 86%
“…engagement in resistance training, when strength was excluded from the model. This is consistent with the observations that skeletal muscle mass was inversely associated with FLI values [32] and that muscle fat accumulation correlated with NASH severity [33]. Altogether, these data point to a role of skeletal muscle, in addition to adipose tissue, in the pathogenesis of NAFLD.…”
Section: Mechanisms Of Exercise-induced Reduction In Fli and Vaisupporting
confidence: 86%
“…Recent cross-sectional studies revealed the association between sarcopenia and NAFLD in general population [17][18][19]. To our knowledge, this is the first study to investigate the association between SMI and hepatic steatosis in patients with type2 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…We obtained readings for skeletal muscle mass (SMM, kg) and visceral fat area (VFA, cm 2 ). Skeletal muscle mass index (SMI, %) was expressed as percent, dividing the SMM (kg) by total body weight (kg) [17][18][19].…”
Section: Measurement Of Body Composition Determined By Bioelectric Immentioning
confidence: 99%
“…NALFD is associated with sarcopaenia and individuals with low muscle mass have a higher risk of developing NAFLD (63,64). Given the well-described detrimental effects GCs have on muscle, an indirect mechanism of NAFLD from myokine secretion, protein mediator or increased insulin resistance is plausible (20,65).…”
Section: Glucocorticoids Nafld and Musclementioning
confidence: 99%